'I'm fine!': Assertions of lack of support need among patients with chronic obstructive pulmonary disease: A mixed-methods study. (September 2022) - Gardener, A Carole; Moore, Caroline; Farquhar, Morag; Ewing, Gail; Massou, Efthalia; Duschinsky, Robbie
Objectives: To understand how people with Chronic Obstructive Pulmonary Disease (COPD) disavow their support needs and the impact on care. Methods: Two stage mixed-method design. Stage 1 involved sub-analyses of data from a mixed-method population-based longitudinal study exploring the needs of patients with advanced COPD. Using adapted criteria from mental health research, we identified 21 patients who disavowed their needs from the 235 patient cohort. Qualitative interview transcripts and self-report measures were analysed to compare these patients with the remaining cohort. In stage 2 focus groups (n = 2) with primary healthcare practitioners (n = 9) explored the implications of Stage 1 findings. Results: Patients who disavowed their support needs described non-compliance with symptom management and avoidance of future care planning (qualitative data). Analysis of self-report measures of mental and physical health found this group reported fewer needs than the remaining sample yet wanted more GP contact. The link between risk factors and healthcare professional involvement present in the rest of the sample was missing for these patients. Focus group data suggested practitioners found these patients challenging. Discussion: This study identified patients with COPD who disavow their support needs, but who also desire more GP contact. GPs report finding these patients challenging to engage.